PENGARUH PEMBERIAN PERASAN Sechium edule (Jacq.) Swartz TERHADAP KADAR KOLESTEROL TOTAL DAN TRIGLISERIDA SERA MENCIT QUECKERBUS - Wahjo Dyatmiko; Suprapto Maat; Idha Kusumawati; Anang Teguh Eko Santoso (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
This research was an effort to reveal the effect of fruit juice of ‘labu siam’ [Sechium edule (Jacq.) Swartz] on total cholesterol and total glyceride of mice serum and also to reveal the secondary metabolites content of the juice. In this research, four groups of mice each consist of 8 was used. First group ws given normal food, the second group was given hyperlipidemic inducer. The third group was given hyperlipidemic inducer and fruit juice at dosage 0.546 mg/kg b.w. The third group was given hyperlipidemic inducer and fruit juice at dosage 1.092 mg/g b.w. The exogenic and endogenic hyperlipidemic inducers used were cholesterol suspension and propyl thiouracyl 0.01%, espectively. Both the inducer and the juice were given every day orally for three weeks. At the last day, the mice were fasted for 12-24 hours and the blood was collected intracardially. Assay of cholesterol and triglyceride in the sera was carried out using the reagent kits.Statistical analysis shows that the administration of the fruit juice of ‘labu siam’ at dosage 0.546 mg/g and 1.092 mg/g b.w. can decrease the triglyceride concentration in the sera. The dose 0.546 mg/g decreases the total cholesterol concentration, but the dose 1.092 mg/g did not show the sera cholesterol decreasing activity. Phytochemical screening for the constituents of the juice indicated that the juice contains saponin glycosides.